Development of Choroidal Neovascularization in rats with Advanced Intense Cyclic Light-induced Retinal Degeneration - Albert, Daniel M. (2010)
OBJECTIVE: To study the progressive changes of intense cyclic light-induced retinal degeneration and determine whether it results in choroidal neovascularization (CNV). METHODS: Albino rats were exposed to 12 h of 3000 lux cyclic light for 1, 3, or 6 months. Prior to euthanization, fundus examination, fundus photographs, fluorescein and indocyanine green angiography, and Optical Coherence Tomography (OCT) evaluations were performed. Light exposed animals were euthanized after 1, 3, or 6 months for histopathological evaluation. Retinas were examined for the presence of 4-hydroxy-2-nonenal (HNE) and nitrotyrosine modified proteins by immunofluorescence staining. RESULTS: Chronic intense cyclic light exposure resulted in retinal degeneration with loss of the outer segments of photoreceptors and approximately two-thirds of the outer nuclear layer (ONL) and development of sub-retinal pigment epithelium (RPE) neovascularization after 1 month. Almost the entire ONL was absent with the presence of CNV, which penetrated Bruch’s membrane and extended into the outer retina after 3 months. Absence of the ONL, multiple foci of CNV, RPE fibrous metaplasia, and connective tissue bands containing blood vessels extending into the retina were observed after 6 months. All intense light exposed animals showed an increased presence of HNE and nitrotyrosine staining. OCT and angiographic studies confirmed retinal thinning and leakiness of the newly fromed blood vessels. CONCLUSIONS: Our results suggest albino rats develop progressive stages of retinal degeneration and CNV after chronic intense cyclic light exposure allowing the detailed study of the pathogenesis and treatment of age-related macular degeneration.